Self-Efficacy dengan Tingkat Kecemasan Menghadapi Persalinan pada Ibu Hamil Trimester III di Klinik Wirati - Yeninda Septieny Sitepu; Gusti Ayu Marhaeni; I Nyoman Wirata; Ni Made Dwi Mahayati; Listina Ade Widya Ningtyas (Journal of Health Education and Literacy, 2026)
Anxiety about childbirth may affect the psychological preparedness of women in the third trimester of pregnancy. Self-efficacy reflects a woman's confidence in her ability to cope with pregnancy and childbirth and may therefore be associated with anxiety levels. This study aimed to analyze the relationship between self-efficacy and anxiety in facing childbirth among women in the third trimester of pregnancy. An analytic correlational study with a cross-sectional approach was conducted at Wirati Clinic from March 3 to May 8, 2025. The sample comprised 30 third-trimester pregnant women selected using total sampling. Data were collected using a 35-item self-efficacy questionnaire and the 10-item Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAQ-R2). The relationship was analyzed using Spearman's rank correlation. Most respondents were aged 20–35 years (93.3%), had higher education (70.0%), and were employed (60.0%). Self-efficacy was most frequently categorized as moderate (46.7%), while anxiety was most frequently categorized as moderate (56.7%). A moderate negative correlation was found between self-efficacy and anxiety level (r_s = -0.424; p = 0.019). Higher self-efficacy was associated with lower anxiety about childbirth among the study participants.